Pengaruh Penambahan Gula dan Amonium Sulfat terhadap Kualitas Nata de Soya - Anshar Patria; Murna Muzaifa; Zurrahmah Zurrahmah (Agricultural Faculty, 2013)
This research aims to utilize of tofu liquid waste (Whey) into a more economical product in the form of nata de soya . This research uses a complete randomized design, which is consists of two factors, namely sugar (6% , 8% and 10%) and ammonium sulfate (0.3% , 0.5% and 0.7%). The observed parameters included yield, thickness, compressive strength analysis, crude fiber and organoleptic. The analysis results showed that sugar concentration and ammonium sulfate concentration significantly different to the yield, thickness, crude fiber, compressive strength and organoleptic. This research results showed that sugar and ammonium sulfate concentration influence significantly different to the thickness, crude fiber, compressive strength and organoleptic and not significantly different to the yield of nata de soya. The higher the sugar concentration and ammonium sulfate are used, the higher the yield, thickness, compressive strength, crude fiber produced. The best results obtained in the treatment of 10% sugar concentration and 0.7% ammonium sulfate.